Injil Yohanes :Kristologi dan Iman Jemaat Perdana (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to explore Christology in the Gospel of John, specifically the identity of Jesus as the pre-existent Word (Logos), His incarnation, the claim to divinity through the statement